Feminist Reading of Kamala Das’s Poetry: Exploring Feminine Sensibility in Kamala Das's Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Kamala Das has a place with the original of modern English poets who developed another poetics for themselves and made another begin both in theme and strategy around 1960's. In Kamala Das' poetry we locate the best articulation of feminine sensibility, its concealment in a male dominated society. So her poetry is confession booth and self-portraying, all things considered, however on occasion she universalizes what is close to home. She renounced the age-old and to some degree sterile aestheticism for a freedom of brain and body. The male fantasia in poetry enjoys different complex highlights and shared thematic domains concerning the universe of men, while female capriccio in poetry spins around the bunch the matic enunciations concerning the residential life, societal collaborations and the self of a woman. Her poetry passes on her antipathy for male domination and to the phonies.